Collaboration Between Teachers and Parents in Shaping the Islamic Character of Senior High School Students - Hafiz, Sylva Rahmah; Nurmawati, Nurmawati (Universitas Pendidikan Indonesia, 2024)
This study aims to determine the form of cooperation between teachers and parents, to determine the supporting factors and obstacles in forming Islamic character in students at SMAS IT Al Hijrah 2. The method used in this study uses a qualitative approach with a descriptive method, for data collection techniques in this study using observation, interviews, and documentation. For samples taken from the results of interviews with the principal, PAI teachers, homeroom teachers, parents as informants and some documentation as supporting data. The results of this study indicate that to form student character, several supporting activities can be carried out, and require a close relationship between teachers at school and parents at home. Supporting factors in forming student character are the availability of adequate facilities and infrastructure, open communication between teachers, parents and students and a conducive school environment. While the inhibiting factors are the inconsistency of students in carrying out worship, the environment of friends at home can influence, and family factors that do not fully support students.